2013
DOI: 10.1186/1477-7819-11-195
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival after resection of pancreatic ductal adenocarcinoma with para-aortic lymph node metastasis: case report

Abstract: Pancreatic cancer patients with para-aortic lymph node metastasis have a poor prognosis and patients living longer than 3 years are rare. We had a patient with pancreatic cancer who survived for more than 10 years after removal of the para-aortic lymph node metastasis. A 57-year-old woman was diagnosed with pancreatic head cancer and underwent a pancreaticoduodenectomy with subtotal gastric resection following Whipple reconstruction in 2000. Para-aortic lymph node metastasis was detected during the operation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…This fact is mainly correlated with the high capacity of the pancreatic adenocarcinoma to spread via lymphatic route; therefore, it has been demonstrated that lymph node metastases develop early in the course of disease in pancreatic adenocarcinomas and represent one of the most important prognostic factors for the long-term survival. However, the extent of the lymph node dissection has been permanently debated, different opinions being reported so far; while the European countries sustain the idea that an extended lymph node dissection in pancreatic adenocarcinoma does not improve the survival and, moreover, increases the postoperative morbidity rates, the Eastern countries consider that such a lymph node dissection is perfectly justified in order to increase the chances for an improved survival [13][14][15][16][17] .…”
Section: Pancreatic Tumor Resection and Lymph Node Dissection In Pancmentioning
confidence: 99%
“…This fact is mainly correlated with the high capacity of the pancreatic adenocarcinoma to spread via lymphatic route; therefore, it has been demonstrated that lymph node metastases develop early in the course of disease in pancreatic adenocarcinomas and represent one of the most important prognostic factors for the long-term survival. However, the extent of the lymph node dissection has been permanently debated, different opinions being reported so far; while the European countries sustain the idea that an extended lymph node dissection in pancreatic adenocarcinoma does not improve the survival and, moreover, increases the postoperative morbidity rates, the Eastern countries consider that such a lymph node dissection is perfectly justified in order to increase the chances for an improved survival [13][14][15][16][17] .…”
Section: Pancreatic Tumor Resection and Lymph Node Dissection In Pancmentioning
confidence: 99%
“…Evidence suggests that metastasis to lymph nodes is an early event in pancreatic cancer progression, and presence of tumor cells in lymph nodes represents one of the most negative prognostic factors with respect to patient outcomes [8,27,29,37,60–63]. Conservative surgical views support the standard PD with loco-regional lymphadenectomy [27,31,34,36,38,42,56,59,64–74], while others, most notably numerous Japanese groups, advocate that a more radical PD with extensive removal of retroperitoneal soft tissue and extended lymphadenectomy [27,34,39,42,75–84] results in better patient outcomes. Collected studies in Table 1 [8,27,31,34,36,37,39,40,42,59,64–75,77–99] demonstrate the broad range of study designs and conclusions that have fueled this debate.…”
Section: Pancreatic Tumor Resection and Lymphadenectomymentioning
confidence: 99%
“…Conservative surgical views support the standard PD with loco-regional lymphadenectomy [27,31,34,36,38,42,56,59,64–74], while others, most notably numerous Japanese groups, advocate that a more radical PD with extensive removal of retroperitoneal soft tissue and extended lymphadenectomy [27,34,39,42,75–84] results in better patient outcomes. Collected studies in Table 1 [8,27,31,34,36,37,39,40,42,59,64–75,77–99] demonstrate the broad range of study designs and conclusions that have fueled this debate. A recent set of randomized, controlled clinical trials from several centers around the world and a mathematical model of outcomes prediction have concluded that extended lymphadenectomy does not improve survival over traditional, more conservative resection and that quality-of-life may be decreased with more radical surgery [67–70,72,74,81,83,87,88,95].…”
Section: Pancreatic Tumor Resection and Lymphadenectomymentioning
confidence: 99%
See 2 more Smart Citations